Validation of the RELAP5 code for the simulation of the Siphon Break effect in pool type research reactors - BELCHIOR JUNIOR, ANTONIO (2020)
In an open pool type reactor, the pool water inventory should act as a heat sink to provide emergency reactor core cooling. In the Brazilian Multipurpose Reactor ??? RMB, to avoid the loss of pool water inventory, all the Core Cooling System (CCS) lines penetrate at the pool top, far above the reactor core level. However, as most of CCS equipment and lines are located below the reactor core level, in the case of a Loss of Coolant Accident (LOCA), a large amount of pool water could be lost drained by siphon effect. To avoid RMB research reactor core discovering in the case of a LOCA, siphon breakers, that allow CCS line air intake, are installed in the CCS lines in order to stop the reactor pool draining due to siphon effect. As siphon breakers are important passive safety devices, their effectiveness should be verified. Several previous numerical and experimental studies about siphon break effect were found in the literature. Some of them comment about the effectiveness of the siphon breakers based on their air intake area. Others state that one-dimensional thermo-hydraulic system codes such as RELAP5 code would fail when modeling the siphon break effect. This work shows the RELAP5/MOD3.3 code capability in modeling the siphon break effect. A nodalization for RELAP5/MOD3.3 code of a Siphon Breaker Test Facility located at POSTECH University in Korea was developed. Experiments considering several siphon breakers device intake areas were simulated. A very good agreement between numerical and experimental results was obtained. As siphon breakers intake areas decrease, the siphon breaker effectiveness also decreases and more water is drained from the reactor pool. For smaller siphon breaker intake areas, RELAP5/MOD3.3 code showed conservative results, overestimating the reactor pool water losses.